Nanohyperthermia of malignant tumors. II. In vivo tumor heating with manganese perovskite nanoparticles - Bubnovskaya, L.; Belous, A.; Solopan, A.; Podoltsev, A.; Kondratenko, I.; Kovelskaya, A.; Sergienko, T.; Osinsky, S. (Experimental Oncology, 2012)
Objectives: To evaluate the ability of manganese perovskite nanoparticles (lanthanum-strontium manganite) to heat the tumor tissue in vivo under action of external alternating magnetic field. Materials and Methods: The magnetic fluid on the basis of nanoparticles of perovskite manganite was tested in the heating experiments using of alternating magnetic field of frequency 300 kHz and amplitude 7.7 kA/m. Guerin carcinoma was transplanted into the muscle of rat. Magnetic fluid was injected intramuscularly or intratumorally. Temperature was measured by copper-constantan thermocouple. Results: Temperature of magnetic fluid was increased by 56 °C for 10 min of alternating magnetic field action. Administration of magnetic fluid into the muscle followed by alternating magnetic field resulted in the elevation of muscle temperature by 8 °C after 30 min post injection. Temperature of the tumor injected with magnetic fluid and treated by alternating magnetic field was increased by 13.6 °C on the 30 min of combined influence. Conclusion: In vivo study with rat tissue has demonstrated that magnetic fluid of manganite perovskite injected in the tumor increases the tumor temperature under an alternating magnetic field. Obtained results emphasize that magnetic fluid of manganite perovskite can be considered as effective inducer of tumor hyperthermia.